The effect of two golimumab doses on radiographic progression in ankylosing spondylitis: results through 4 years of the GO-RAISE trial. Issue 6 (3rd May 2013) - Braun, Jürgen; Baraliakos, Xenofon; Hermann, Kay-Geert A; Deodhar, Atul; van der Heijde, Désirée; Inman, Robert; Beutler, Anna; Zhou, Yiying; Xu, Stephen; Hsu, Benjamin
Abstract : Objective: To evaluate radiographic progression in patients with ankylosing spondylitis (AS) receiving two different doses of the tumour necrosis factor antagonist golimumab. Methods: 356 patients with AS were randomly assigned to placebo, or golimumab 50 mg or 100 mg every 4 weeks (wks). At wk16, patients with inadequate response early escaped with blinded dose adjustments (placebo→golimumab 50 mg, 50 mg→100 mg). At wk24, patients still receiving placebo crossed over to golimumab 50 mg. Lateral view radiographs of the cervical/lumbar spine were obtained at wk0, wk104 and wk208, and scored (two blinded readers, modified Stoke AS Spine Score (mSASSS)). Observed data were used for wk104 analyses; missing wk208 scores were linearly extrapolated. Results: Wk104 changes from baseline in mSASSS averaged 1.6±4.6 for placebo crossover, 0.9±2.7 for 50 mg and 0.9±3.9 for 100 mg. By wk208, following golimumab therapy for 3.5–4 years, mean changes in mSASSS were 2.1±5.2 for placebo crossover, 1.3±4.1 for 50 mg and 2.0±5.6 for 100 mg. Less than a third of patients (placebo crossover, 19/66 (28.8%); 50 mg, 29/111 (26.1%); 100 mg, 35/122 (28.7%)) had a definitive change from baseline mSASSS (>2). Less radiographic progression was observed through wk208 in patients without baseline syndesmophytes (0.2 vs 2.8 in patients with ≥1 syndesmophyte; p<0.0001) and with baseline C-reactive protein (CRP) levels ≤1.5 mg/dl (0.9 vs 2.9 with CRP >1.5 mg/dl; p=0.0004). Conclusions: No difference in mSASSS change was observed between golimumab 50 mg and 100 mg. The radiographic progression rate remained stable at years 2 and 4, suggesting no acceleration of new bone formation over time. Golimumab-treated AS patients with no syndesmophytes and less systemic inflammation at baseline had considerably less radiographic progression.